Pengaruh biaya promosi dan kebijakan penetapan harga terhadap peningkatan penjualan (Studi pada PT Granitoguna Building Ceramics) - Bakti Toni Endaryono; Tjipto Djuhartono (Universitas Indraprasta PGRI, 2021)
This study was conducted aiming to determine the extent of the influence of pricing policies on increasing sales at PT Granitoguna BC, the research method used was to use quantitative methods with data analysis techniques using multiple correlation regression equations, interview data collection techniques, documentation and observation, as for the analysis used as a hypothesis is a multiple correlation regression equation, the correlation coefficient of determination.Based on multiple linear regression equation analysis results obtained Y = 64.85 + 0.3 X1 + 4.36 X2, multiple linear coefficients obtained results: R1y = 0.99 and R2y = 0.90 and the determination coefficient results are Kd = 81 ,% that the increase in sales at PT Granitoguna BC is influenced by promotions, thus to increase company sales, promotion is an important tool to achieve company goals in this case increase sales.